2015
DOI: 10.1016/j.jprot.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Urine, peritoneal fluid and omental fat proteomes of reproductive age women: Endometriosis-related changes and associations with endocrine disrupting chemicals

Abstract: Endometriosis, ectopic growth of the uterine lining (endometrium), which affects 6–11% of reproductive age women, is associated with pelvic pain and infertility. We investigated the peritoneal fluid (PF), urine and omental fat (OF) proteomes of women with endometriosis vs. individuals with no surgically visualized endometriosis. All participants were enrolled in the NICHD-funded ENDO Study. A two-step proteomic study was performed. The first, a broad survey, employed a semi-quantitative gel LC-mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
(71 reference statements)
0
11
0
1
Order By: Relevance
“…Western blot analyses were performed to validate the proteomics results . The protein samples were separated by 10% SDS‐PAGE gels and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analyses were performed to validate the proteomics results . The protein samples were separated by 10% SDS‐PAGE gels and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that endometriosis is prevalent after menarche and dramatically drops after menopause, which has led researchers to believe that the disorder is estrogen and progesterone dependent . Risk factors known to be associated with endometriosis include age, family history, educational attainment, age at menarche, and exposure to endocrine‐disrupting chemicals . Life style factors such as alcohol/caffeine intake, smoking, and physical activity influence oestrogen levels in the body and, therefore, may impact development of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic inflammation associated with obesity and diseases such as HIV are known to increase the size and immune cell content of the omentum [111, 112]. Compared to disease-free women, Williams et al [113] observed alterations in omental proteinase expression of women with endometriosis, which correlated with increased body burden of several EDCs (although TCDD was not examined). As shown in Figure 3, compared to control animals, F1 and F3 mice exhibit a marked accumulation of immune cells within the omentum, supporting our hypothesis that these animals have a heightened “baseline” inflammatory phenotype.…”
Section: Transgenerational Reproductive Dysfunction In a Mouse Modelmentioning
confidence: 99%